The Introduction of a Supermarket via Tax-Credits in a Low-Income Area: The Influence on Purchasing and Consumption. Issue 1 (January 2017) - Elbel, Brian; Mijanovich, Tod; Kiszko, Kamila; Abrams, Courtney; Cantor, Jonathan; Dixon, L. Beth
Purpose: Interest and funding continue to grow for bringing supermarkets to underserved areas, yet little is known about their impact. Design: A quasi-experimental study was used to determine the impact of a new supermarket opening as a result of tax and zoning incentives. Setting: The study took place in the South Bronx, New York City, New York. Subjects: Studied were residents of two South Bronx neighborhoods deemed high need. Measures: Food purchasing and consumption were examined via surveys and 24-hour dietary recalls before and at two points after the supermarket opened (1–5, 13–17 months). Analysis: Data were analyzed using difference-in-difference models controlling for gender, race and ethnicity, age, education, marital status, and self-reported income. Ordinary least squares and logistic regression models were estimated for continuous and binary outcomes, respectively. Results: At baseline, 94% to 97% of consumers shopped at a supermarket. There was a 2% increase in this behavior in the intervention community ( p < .05) not seen in the comparison community. One year later there was a 7% net increase in eating at home ( p < .1) and a 20% decrease in drinking sugary beverages ( p < .05), but no appreciable change in fruit/vegetable consumption or overall dietary quality. Conclusion: The new supermarket did not result in substantial or broad changes in purchasing patterns or nutritional quality of food consumed, though smaller, positive changes were observed over a 1-year period. Future work should examine different contexts and a broader set of outcomes, including economic development.